2016
DOI: 10.1186/s12995-016-0144-3
|View full text |Cite
|
Sign up to set email alerts
|

Hydrofluoric acid burns in the western Zhejiang Province of China: a 10-year epidemiological study

Abstract: BackgroundChemical burns caused by hydrofluoric acid (HF) frequently occur in the Western Zhejiang Province. This study aimed to investigate the epidemiological characteristics of HF burns within this region.MethodsA 10-year retrospective analysis was conducted using data from all inpatients with HF burns. These patients were treated at the Department of Burns and Plastic Surgery at our hospital between January 2004 and December 2013. Information obtained for each patient included sex, age, occupation, burn lo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
12
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 28 publications
(39 reference statements)
0
12
0
Order By: Relevance
“…A 10-year [ 1 ], a 11-year [ 20 ], a 15-year [ 30 ], a 20-year [ 2 ] and a 22-year [ 29 ] retrospective epidemiological studies revealed that chemical burns encountered in a Burn centres caused by hydrofluoric acid are one with the most frequent occurrence, especially in the regions with highly developed industry. The most common sites of injury are the head and neck, hands, legs and arms [ 1 ], [ 45 ]. HF burns might be accompanied by ocular injuries, respiratory and digestive tract disorders [ 1 ].…”
Section: Corrosiveness and Toxicitymentioning
confidence: 99%
See 4 more Smart Citations
“…A 10-year [ 1 ], a 11-year [ 20 ], a 15-year [ 30 ], a 20-year [ 2 ] and a 22-year [ 29 ] retrospective epidemiological studies revealed that chemical burns encountered in a Burn centres caused by hydrofluoric acid are one with the most frequent occurrence, especially in the regions with highly developed industry. The most common sites of injury are the head and neck, hands, legs and arms [ 1 ], [ 45 ]. HF burns might be accompanied by ocular injuries, respiratory and digestive tract disorders [ 1 ].…”
Section: Corrosiveness and Toxicitymentioning
confidence: 99%
“…The most common sites of injury are the head and neck, hands, legs and arms [ 1 ], [ 45 ]. HF burns might be accompanied by ocular injuries, respiratory and digestive tract disorders [ 1 ].…”
Section: Corrosiveness and Toxicitymentioning
confidence: 99%
See 3 more Smart Citations